The Development of Portfolio Based Short Text Writing Assessment Instrument in 11th Grade of Senior High School (SMAN 1) Panai Tengah - Sri Lestari Siregar; M. Oky F. Gafari; Malan Lubis (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This research produces a portfolio-based short story writing assessment instrument. The research method used is the Research and Development method which refers to the development of Borg and Gall (in Tegeh et al, 2014: 7-13). The module development process is carried out with three stages: a preliminary study stage, initial product development and product trials. The results showed that the feasibility assessment by material experts consisted of 4 aspects namely content feasibility aspects obtained an average of 77 with effective criteria, aspects of the feasibility of the presentation obtained an average of 92.5 with very effective criteria, aspects of language eligibility obtained on average 77 with effective criteria, and aspects of contextual assessment obtained an average of 79.9 with effective criteria, evaluation of eligibility by instrument evaluation experts obtained an average of 85 with very effective criteria. The assessment interprets the meaning of the short story text, both verbally and in writing fulfilling the reliable criteria with a reliability of 0.7, the Assessment identifies the abstract, orientation, complications, resolution, evaluation, and koda meets the reliable criteria with a reliability of 0.7 and the assessment of writing the story text short meet the reliable criteria with a reliability of 0.97. This research impacts on the use of portfolio-based short story writing assessment instruments.